Climate Change, Mining and Traditional Indigenous Knowledge in Australia - Tony Birch (Social Inclusion, 2016)
Australia, in common with nations globally, faces an immediate and future environmental and economic challenge as an outcome of climate change. Indigenous communities in Australia, some who live a precarious economic and social existence, are particularly vulnerable to climate change. Impacts are already being experienced through dramatic weather events such as floods and bushfires. Other, more gradual changes, such as rising sea levels in the north of Australia, will have long-term negative consequences on communities, including the possibility of forced relocation. Climate change is also a historical phenomenon, and Indigenous communities hold a depth of knowledge of climate change and its impact on local ecologies of benefit to the wider community when policies to deal with an increasingly warmer world are considered. Non-Indigenous society must respect this knowledge and facilitate alliances with Indigenous communities based on a greater recognition of traditional knowledge systems.